2021
DOI: 10.1111/ijcp.14434
|View full text |Cite
|
Sign up to set email alerts
|

Promising effects of atorvastatin on mortality and need for mechanical ventilation in patients with severe COVID‐19; a retrospective cohort study

Abstract: Purpose Considering the anti‐inflammatory effect of atorvastatin and the role of medical comorbidities such as hypertension and coronary artery disease on the prognosis of the COVID‐19 patients, we aimed to assess the effect of atorvastatin add‐on therapy on mortality caused by COVID‐19. Methods We conducted a retrospective cohort study, including patients who were hospitalised with confirmed diagnosis of severe COVID‐19. Baseline characteristics and related clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(48 reference statements)
0
7
0
1
Order By: Relevance
“…This finding is consistent with that observed in numerous studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with that observed in numerous studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…In total, 36 of 49 studies (73%) show a lower risk of severe COVID‐19 outcomes––in particular mortality––among statin users compared with nonusers. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 In 11 studies, ratio measures were close to 1. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 In 2 studies, an increased risk was observed.…”
mentioning
confidence: 95%
“…Along the same line, statins have prominent in vivo effects on endothelial cell biology and it has been discussed whether they would be able to act on vascular dysfunction associated with COVID-19 [49]. Considering its role in hypertension and coronary disease, ATV was assessed retrospectively in severe COVID-19 patients having comorbidities, with good results in terms of reducing the need for mechanical ventilation and in-hospital mortality [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that statins may play a role in the treatment of SARS-CoV-2 infection, mainly by reducing complications due to pre-existing atherosclerotic cardiovascular disease and preventing acute lung injury [ 57 , 58 , 59 ]. Indeed, several observational clinical studies and meta-analyses have demonstrated a significant protective effect of statins in COVID-19 patients, administrated before or during hospitalization, reducing the risk of the need for invasive mechanical ventilation, mortality, ARDS, and hospital stay [ 3 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Overall, these studies suggest that this class of drugs may represent an important choice for adjuvant therapy in the treatment of these patients, influencing their course favorably.…”
Section: Discussionmentioning
confidence: 99%